Less is more: The horror of suggestion in Jacques Tourneur's Cat People. Issue 1 (1st March 2021) - Parrish, Jordan
Someone, or something, is following Alice (Jane Randolph). In the famous scene from Jacques Tourneur's Cat People (1942), Irena (Simone Simon), who is married to the man with whom Alice just went out, tails Alice as she walks home. While Irena appears to stop following her at one point, it is here that Alice notices she is being followed by something else. She sees and hears nothing, but somehow feels that something, invisible, unseen, is nevertheless in close proximity. Certainly a classic horror scene, Tourneur nevertheless takes here an unusual approach to scaring audiences. Instead of directly showing its horror element, Irena as a cat person, Cat People instead suggests its presence. The subtle way in which Tourneur films this horrific scene seems at odds with conventional definitions of the horror genre, frequently defined in scholarship by its depictions of excess. By reorienting our relation to the horror genre in this way, Tourneur creates a concept that forces us to rethink the genre's parameters, aspects and definitions. This article argues that Tourneur's films centre around a main concept, suggestion and that this conceptual creation makes him, in turn, a philosopher of horror who pushes our understandings of the genre into unconventional directions. Through a close analysis of suggestive horror in Cat People and his other films, I argue that this suggestive style of horror is just as effective and horrific as the excessive one, that it is neither better nor worse, but achieves similar ends through different means. The article proceeds with three main objectives: to define Tourneur's concept of suggestion with the associated problem of caricature to which it responds, to delineate the formal ways that Tourneur's horror philosophy appears in suggestion-images and to place Tourneur's philosophy of suggestion in conversation with existing horror scholarship that defines the genre through excess. By doing so, I argue that Tourneur's philosophy, as evidenced in Cat People, forces us to think differently about the horror genre than ways which posit excess as its defining feature, ultimately envisioning a heretofore untheorized aspect of the genre: the horror of suggestion.